2004
DOI: 10.1002/qua.20346
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of neutral and cationic complexes involving phenol

Abstract: Geometry and interaction energy in complexes of the Ph-L type (L ϭAr, N 2 , CO, H 2 O, NH 3 , CH 4 , CH 3 OH, CH 3 F) involving neutral or cationic phenol were determined using the density functional theory formalism based on the minimization of the total energy bifunctional and gradient-dependent approximations for its exchangecorrelation and nonadditive kinetic-energy parts. For the neutral complexes the calculated interaction energies range from 1 kcal/mol for the Ph-Ar complex to about 10 kcal/mol for Ph-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…In addition, high-level quantum chemical calculations of the potential energy surface in the S 0 state yield a -bonded global minimum, and it is unclear at present whether the H-bonded structure is a shallow local minimum or a transition state. [17][18][19][20] Comparison of rotational constants derived from a rotational band contour fit of the S 1 origin spectrum with ab initio rotational constants obtained at the MP2 / 6-31G͑d , p͒ level also support a -bonded ͑1 ͉ 0͒ geometry for n =1. 21 Meerts et al 6 presented the fully rotationally resolved electronic spectrum of the 7D-phenol-Ar 1 cluster, without a detailed structural analysis.…”
Section: Introductionmentioning
confidence: 65%
“…In addition, high-level quantum chemical calculations of the potential energy surface in the S 0 state yield a -bonded global minimum, and it is unclear at present whether the H-bonded structure is a shallow local minimum or a transition state. [17][18][19][20] Comparison of rotational constants derived from a rotational band contour fit of the S 1 origin spectrum with ab initio rotational constants obtained at the MP2 / 6-31G͑d , p͒ level also support a -bonded ͑1 ͉ 0͒ geometry for n =1. 21 Meerts et al 6 presented the fully rotationally resolved electronic spectrum of the 7D-phenol-Ar 1 cluster, without a detailed structural analysis.…”
Section: Introductionmentioning
confidence: 65%
“…Intermolecular bonding for PhOH-Ar is in agreement with high level quantum chemical calculations. 19,43,44 Very recently, hole-burning spectra of PhOH-Ar and PhOH -Ar 2 showed that only one isomer is present in a molecular beam expansion. 45 The intermolecular vibrational structure in the cationic D 0 state of PhOH + -Ar obtained in ZEKE and MATI spectra was assigned assuming a -bound structure, and an accurate value for the dissociation energy of -bound PhOH + -Ar was derived as 535± 3 cm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the PW91k kinetic energy functional 11,12 employs the analytical form of the Perdew-Wang ͑PW91͒ exchange functional, 22 and the TW02 functional 14 and the PBE2, PBE3, and PBE4 functionals 9 utilize the form suggested by Becke. 23 These functionals have been shown to successfully describe weakly interacting systems and coordination compounds.…”
Section: Orbital-free Embedded Dftmentioning
confidence: 99%
“…4 This term, which is typically largest for cases in which the subsystem densities are strongly overlapping, 9 is a significant source of error in many e-DFT calculations, and it generally limits the method to applications in which the subsystem densities involve nonbonded or weakly interacting molecular groups. 4,9,10 Although encouraging progress towards the accurate calculation of the nonadditive kinetic energy contribution have been reported, 9,[11][12][13][14][15][16] more work in this direction is needed.…”
Section: Introductionmentioning
confidence: 99%